La toponymie de l'Ile d'Orléans - Poirier, Jean (Cahiers de géographie du Québec, 1962)
The writer situates the Island of Orleans and briefly describes its physiography and history of settlement. The toponymy imposed during the early French regime (toponymie primitive)is described —with a few notable exceptions {Orléans, Argentenay, Beaulieu and Cap de Condé) these place names have almost entirely disappeared. Much of the present toponymy was established after 1666 and originates principally from Catholic parish names and from local usage. The major place names of the island were imposed by Church authorities but the minor toponyms were created by the local inhabitants. The island's toponymy is described as dynamic because many of the original place names have either been replaced or altered. The writer is of the opinion that toponymy should conform with reality ; consequently he deplores the fact that local usage is frequently ignored on contemporary maps of the Island of Orleans. An index of place names of the Island of Orleans is appended to the text.